The Effectiveness of the Gobak Sodor Digital Encyclopedia in Preserving Traditional Sports and Improving Student Learning Outcomes - Setiawahyu, Mochamad Iman; Nugroho, Wahyu Adhi; Sugianto, Sugianto (Indonesian Journal of Physical Education and Sport Science, 2025)
Studi pupose. Traditional games are a cultural heritage rich in educational value, one of which is Gobak Sodor. However, technological developments have led to traditional games being increasingly abandoned. This study aims to develop and test the effectiveness of the Gobak Sodor Digital Encyclopedia (Gocir Pedia) in preserving culture while improving student learning outcomes. Materials and methods. The research method used the ADDIE (Analyse, Design, Development, Implementation, Evaluation) development model. Product validation involved three expert validators (physical education, learning technology, and digital media). Research instruments included (1) expert validation, (2) learning outcome tests (pre-test and post-test) using the digital encyclopaedia, (3) observation sheets and interviews. The population and sample consisted of all 20 students taking traditional learning courses. Data analysis techniques used quantitative and qualitative methods: (a) analysed using the Content Validity Index (CVI), (b) N-Gain, and (c) t-test. Qualitative data consisted of comments from experts and students after using the product. Results. The average research result was 91.8% (excellent category). A limited trial was conducted on 20 Physical Education, Health, and Recreation students. The test results showed an average pretest score of 9.35 and a posttest score of 17.45, with an N-Gain of 0.78 (high category). The paired t-test showed a significant difference (t = 42.50; p < 0.05). Conclusion. Thus, this digital encyclopaedia is effective as an educational medium and a means of preserving the traditional Gobak Sodor sports culture.